The Model of Educational Reconstruction: Students’ Conceptual Knowledge on Solid State Chemistry Domain - Nursa'adah, E.; Liliasari, L.; Mudzakir, A.; Barke, H. D. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
Solid state chemistry (SSC) concept is abstract yet makes it difficult for students. Considering studentsÃ¢â‚¬â„¢ and scientist conception in designing a learning sequence, it is important to make scientific knowledge to be comprehensible for students. Model of Educational Reconstruction (MER) was adopted to define learning in order to develop studentsÃ¢â‚¬â„¢ Conceptual Knowledge (CK) of the SSC concept. A sequence of learning activities was designed based on the MER.Ã‚Â The purpose of this study was to examine the use of MER in developing studentsÃ¢â‚¬â„¢ CK. One group pre- and post-test experimental design employed in this study. CK on SSC structured essay test consisting of 26 items were developed to measure studentsÃ¢â‚¬â„¢ CK before and after their involvement in learning. Paired sample t-tests were employed and the results showed significant differences in the overall domain-knowledge (p < .001).Ã‚Â In detail, studentsÃ¢â‚¬â„¢ CK categorized into complete (C), incomplete (IC), misconception (M), incorrect (I), and no answer (NA). After the intervention, the number of students that answered correctly increased (57,4% complete and 21% incomplete). This study showed that MER was an effective learning design to develop studentsÃ¢â‚¬â„¢ conceptual knowledge of chemistry concepts.